Acute and sub-chronic toxicity evaluation of the crude methanolic extract of Diospyros mespiliformis hochst ex a. Dc (ebenaceae) and its fractions - Abdullahi Aliyu Ebbo; Dahiru Sani; М. М. Сулейман; Arshad Ahmad; Adamu Zoaka Hassan (2020)
Diospyros mespiliformis, commonly called Jackal berry or African ebony, belongs to the plant family, Ebenaceae. The roots, barks and leaves have been used traditionally to treat wide varieties of conditions, however, there is limited information and literature reports concerning the toxicity and safety of this plant. The present study was conducted to evaluate the acute and sub-chronic toxicity of the crude methanolic extract of Diospyros mespiliformis and its fraction in Wistar rats. Diospyros mespiliformis was extracted by methanol 96 %. The crude methanolic extract was then fractionated into low, average and high polar compounds using hexane, ethyl acetate and butanol respectively. For the acute toxicity study, the revised limit Dose Test of "Up and Down" procedure according to the OECD guideline was used to determine the median lethal dose (LD50) of the crude methanolic leaf and bark extracts using a single fixed dose (5 g/kg) of the extracts administered by oral-gavage sequentially to 5 female Wistar rats. The rats were observed for instant death and toxicity signs for 24 h and then daily for 14 days. In the sub-chronic toxicity study, the bark and leaf ethyl acetate fractions (extract) was administered orally at doses of 250, 500 and 750 mg/kg bw /day respectively for 28 days to healthy Wistar rats. At the end of the experimental period, body weight, certain haematological, serum biochemical and histopathological parameters were evaluated. Results showed that acute oral administration of crude methanolic extract of Diospyros mespiliformis (5 g/kg bw) produced neither mortality nor visible changes in behavior or any other physiological activities and indicated that the LD50 of crude methanolic leaf and bark extract was greater than 5 g/kg bw in Wistar Rats. In the 28-days repeated dose oral toxicity study, no significant toxic effects was detected in any of the parameters evaluated. In conclusion, the crude methanolic extract was found safe in the acute toxicity study and the ethyl acetate fraction of Diospyros mespiliformis in the sub chronic study in rats could be safe for therapeutic purposes over a period not exceeding 28 days.